Effects of Simultaneously Performed Dual-Task Training with Aerobic Exercise and Working Memory Training on Cognitive Functions and Neural Systems in the Elderly - Hikaru Takeuchi; Daniele Magistro; Yuka Kotozaki; Kosuke Motoki; Keyvan Kashkouli Nejad; Rui Nouchi; Hyeonjeong Jeong; Chiho Sato; Salvatore Sessa; Ryoichi Nagatomi; Massimiliano Zecca; Atsuo Takanishi; et al. (Neural Plasticity)
Working memory (WM) training (WMT), aerobic exercise training (AET), and dual-task training improve cognitive functions and alter neural systems in older adults. In particular, the effects have been investigated of dual-task training that combines a walking or standing activity (balance exercise) simultaneously performed with cognitive training (which is ecologically difficult for the elderly). In this study, we investigated the effects of simultaneously performed dual-task training incorporating both AET and WMT (SDAEWMT), using a recumbent ergocycle bicycle and a WMT program that provided a portable console and made the training ecologically easy for the elderly. Older adults (65.9±13.7 years old) participated in 3 months of SDAEWMT, WMT, or AET after random allocation, and the effects of SDAEWMT were compared with those of WMT and AET. Prior to and after training, all the subjects underwent cognitive testing, magnetic resonance imaging (MRI) involving diffusion tensor imaging (DTI), and functional MRI during performance of an N-back WM task. SDAEWMT improved executive function (performance of a frontal assessment battery); however, there was no evidence of broader transfer effects or enhanced learning with WMT. SDAEWMT resulted in mean diffusivity changes in brain areas involving the dopaminergic system, suggesting that neural tissue changes occurred in these areas. SDAEWMT also resulted in an increase in brain activity during the 2-back working memory task in brain areas involved in attentional reorientation. These results suggest that SDAEWMT is effective for improving cognitive functions and inducing beneficial neural changes in older adults.